Ethnomedical and ethnobotanical investigations on the response capacities of Guinean traditional health practioners in the management of outbreaks of infectious diseases: The case of the Ebola virus epidemic. (22nd April 2016) - Baldé, A.M.; Traoré, M.S.; Baldé, M.A.; Barry, M.S.; Diallo, A.; Camara, M.; Traoré, S.; Kouyaté, M.; Traoré, S.; Ouo-Ouo, S.; Myanthé, A.L.; Keita, N.; et al.
Abstract: Ethnopharmacological relevance: The recent outbreak of Ebola virus infections has mostly remained confined to the West African countries Guinea-Conakry, Sierra-Leone and Liberia. Due to intense national and international mobilizations, a significant reduction in Ebola virus transmission has been recorded. While international efforts focus on new vaccines, medicines and diagnostics, no coherent national or international approach exists to integrate the potential of the traditional health practitioners (THPs) in the management of infectious diseases epidemics. Nevertheless, the first contact of most of the Ebola infected patients is with the THPs since the symptoms are similar to those of common traditionally treated diseases or symptoms such as malaria, hemorrhagic syndrome, typhoid or other gastrointestinal diseases, fever and vomiting. Materials and methods: In an ethnomedical survey conducted in the 4 main Guinean regions contacts were established with a total of 113 THPs. The socio-demographic characteristics, the professional status and the traditional perception of Ebola Virus Disease (EVD) were recorded. Results: The traditional treatment of the main symptoms was based on 47 vegetal recipes which were focused on the treatment of diarrhea (22 recipes), fever (22 recipes), vomiting (2 recipes), external antiseptic (2 recipes), hemorrhagic syndrome (2 recipes), convulsion and dysentery (one recipe each). An ethnobotanical survey led to the collection of 54 plant species from which 44 identified belonging to 26 families. The most represented families were Euphorbiaceae, Caesalpiniaceae and Rubiaceae. Literature data on the twelve most cited plant species tends to corroborate their traditional use and to highlight their pharmacological potential. Conclusions: It is worth to document all available knowledge on the traditional management of EVD-like symptoms in order to evaluate systematically the anti-Ebola potential of Guinean plant species. Graphical abstract: